PENGARUH PERGANTIAN MANAJEMEN, OPINI AUDIT, FINANCIAL DISTRESS, UKURAN KAP, DAN UKURAN PERUSAHAAN KLIEN TERHADAP AUDITOR SWITCHING PADA PERUSAHAAN REAL ESTATE DAN PROPERTI DI BURSA EFEK INDONESIA - Vina Kurniaty; Amir Hasan; Yuneita Anisma (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Auditor’s Independence issue is the main cause why companies must do auditor switching mandatorily. Many questions rise when actually there were some companies did voluntary auditor switching outside the rule of auditor switching KMK No. 359/KMK.06/2003 which has been revised to be PMK No. 17/PMK.01/2008. This research is purposed to find empirical evidences about the factors that influence manufacturing companies which are listed in BEI to do voluntary auditor switching. Variables that are used in this research are going change management (CEO), audit opinion (OPINI), financialdistress (DER), KAP size (KAP), client size (LnTA). The data being used is from real estate and Property Company which is listed in BEI in 2007-2012 period. Data collecting method which used in this research is method purposive sampling that based on criteria which has been determined before. Based on the method purposive sampling, research sample total is 14 companies. Hypothesis in this research are tested by logistic regression analytical method. The result of this study it is concluded that client size has significantly effect on auditor switching with negative direction.Otherwise, change in management, audit opinion, financial distress and KAP size do not have significantly effect on the auditor switching.Keywords: Change management, opinion audit, financial distress, KAP size, client size.